Social Factors Influencing Substance and Drug Abuse in Universities in Machakos County, Kenya - Makau, Patricia; Muema, Elizabeth; .Mutuku, Milcah .W (Research on Humanities and Social Sciences, 2019)
The intention of this study was to investigate social factors influencing substance and drug abuse in universities Machakos County, Kenya. The survey study was carried out in Universities in Machakos town. The study was guided by the following objectives: to find out social factors influencing substance and drug abuse in Universities Machakos town and Establish the relationship between gender and drug abuse. The target population comprised of (10,000) students. A sample of (110) respondents was drawn from 5 University college /campuses. Stratified sampling techniques were used to sample (40) female and (70) male students. The research utilized questionnaires as the research instruments. The research instruments were modified after pilot study. The validity and reliability of instruments was established by piloting the instruments in pilot institutions in Machakos University College and Scott university. The reliability of research instrument was determined through the split- half method. The reliability index for the research instrument was 0.78. Qualitative data collected was analyzed descriptively using frequencies and percentages. The main findings of the study were: the prevalence of drug abuse according to gender was male (62.7%) and female (37.3%) and according to university. The social factors contributing drug abuse was peer pressure had (78.2%) and parental and environmental factors (20%). The research also revealed that commonly abused was alcohol with (78%), followed by cigarette (58.5%), followed by illicit brews (50%), miraa (40%), bhang (21%), wines and spirits (15%), finally the least abused drugs were heroin and cocaine with less than 1 percent. On the relationship between gender and drug abuse, the findings reveled that male students three times likely to abuse drugs more than female students. The study made the following recommendations: Government should put in place measures of limiting easy access to drug, Interventions progammes should be designed to halt drug abuse among those who are already abusing drugs and Rehabilitate those who show signs of addiction and finally guidance and counseling strengthened should be strengthened in institutions of learning and especially peer counseling DOI: 10.7176/RHSS/9-20-06